Corporate contributions to education-related causes: Do board characteristics matter? A proposal. - Hashim , Mohd Farid Asraf Md (International Journal of Accounting, Finance and Business, 2025)
The diverse characteristics of board members offer different perspectives on strategy and the implementation of philanthropic initiatives. Since the board of directors plays a key role in shaping corporate philanthropy decisions, further research is needed to explore how board characteristics influence these practices, particularly in the context of education-related causes. Thus, this article suggests a theoretical framework based on resource dependency theory to explore the possible relationship between board size, director independence, education level, field of study, gender diversity, and corporate contributions to education – related causes. The article aims to contribute to the literature on corporate philanthropy and resource dependency theory. Additionally, the recommendations offered may provide valuable insights for companies and stakeholders when assessing board member criteria, focusing not only on general social development but also on supporting the growth of the education sector.